PENGARUH RELATIONSHIP MARKETING DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN (STUDI PADA PELANGGAN PT. NASMOCO PEMUDA SEMARANG BAGIAN SERVIS) - Sefi Lili Amelia; Widayanto Widayanto (Jurnal Ilmu Administrasi Bisnis, 2020)
This study aims to determine the effect of Relationship Marketing and Service Quality on Customer Loyalty through Customer Satisfaction, studies on customers of PT. Nasmoco Pemuda Semarang service section. Relationship Marketing in this study was measured through three dimensions namely Trust, Commitment, and Communication. This type of research is explanatory research. The sampling technique uses non probability sampling techniques with purposive sampling and accidental sampling. Samples taken by 100 respondents PT customers. Nasmoco Pemuda Semarang service section. The study uses a Partial Least Square analysis technique, which is estimated with the WarpPLS 6.0 program. The results of the analysis show that Relationship Marketing, Service Quality and Customer Satisfaction have a positive and significant direct effect on Customer Loyalty. The indirect effect test shows that Relationship Marketing on Customer Loyalty through Customer Satisfaction has a significant positive effect, while Service Quality on Customer Loyalty through Customer Satisfaction has a positive and insignificant influence. Researchers provide advice to the PT. Nasmoco Youth services to improve Relationship Marketing and Service Quality through asking other customer numbers to be contacted, adding training programs to employees, certifying and briefing before working hours reminds again that excellent service is the main goal, holding proof online queues, continuing to provide education customers regarding official workshop fees, providing online/offline space for customer testimonials.